Psychological Well-Being in Building Organizational Commitment - Rian Trinanda Putra; Sulastri; Khairani (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
This study aims to determine the effect of psychological well-being on the commitment of the Intraschool Student Organization (OSIS) administrators at SMKN 2 Bandar Lampung. Low commitment of the Intra-School Student Organization (OSIS) administrators can impact the effectiveness of implementing organizational programs. One of the factors influencing this commitment is psychological well-being, which encompasses self-acceptance, good interpersonal relationships, and personal growth. This study employs a quantitative approach. Data analysis was conducted using simple linear regression to assess the extent to which psychological well-being affects OSIS commitment. The results showed a significant positive influence of psychological well-being on the commitment of OSIS administrators. This indicates that the higher the level of psychological wellbeing, the greater the commitment of OSIS administrators in carrying out organizational activities. Based on these findings, it is recommended that schools pay more attention to student development to enhance commitment to the organization. Keywords: Organizational Commitment; Student Council Members; Psychology Well-Being